2015
DOI: 10.1038/ncomms8135
|View full text |Cite
|
Sign up to set email alerts
|

Strong coronal channelling and interplanetary evolution of a solar storm up to Earth and Mars

Abstract: The severe geomagnetic effects of solar storms or coronal mass ejections (CMEs) are to a large degree determined by their propagation direction with respect to Earth. There is a lack of understanding of the processes that determine their non-radial propagation. Here we present a synthesis of data from seven different space missions of a fast CME, which originated in an active region near the disk centre and, hence, a significant geomagnetic impact was forecasted. However, the CME is demonstrated to be channell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
191
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(205 citation statements)
references
References 67 publications
12
191
0
2
Order By: Relevance
“…After the launch of twin Solar TErrestrial Relations Observatory spacecraft (STEREO: Kaiser et al 2008), the data from the Sun Earth Connection Coronal and Heliospheric Investigation (SECCHI: Howard et al 2008) have enabled us to continuously image CMEs from their lift-off in the corona up to the Earth and beyond Harrison et al, 2012;Liu et al, 2013;Möstl et al, 2015;Vemareddy and Mishra, 2015). These observations have also revealed direct evidence of CME-CME interaction when they are launched in close succession in the same direction Lugaz et al, 2012;Shen et al, 2012;Mishra, Srivastava, and Chakrabarty, 2015).…”
Section: Introductionmentioning
confidence: 84%
“…After the launch of twin Solar TErrestrial Relations Observatory spacecraft (STEREO: Kaiser et al 2008), the data from the Sun Earth Connection Coronal and Heliospheric Investigation (SECCHI: Howard et al 2008) have enabled us to continuously image CMEs from their lift-off in the corona up to the Earth and beyond Harrison et al, 2012;Liu et al, 2013;Möstl et al, 2015;Vemareddy and Mishra, 2015). These observations have also revealed direct evidence of CME-CME interaction when they are launched in close succession in the same direction Lugaz et al, 2012;Shen et al, 2012;Mishra, Srivastava, and Chakrabarty, 2015).…”
Section: Introductionmentioning
confidence: 84%
“…Next, we compare this with the expectation of a self-similar expansion model (e.g. Möstl et al 2015, and references therein) where the shape (axis or shock surface) is simply rescaled with a function of time f (t), so r(λ, t) = f (t) r(λ, t 0 ) where r(λ, t) is the distance to the Sun at λ and time t, and t 0 is a reference time. Then the radial velocity is:…”
Section: Property Variations Along the Icme Frontmentioning
confidence: 99%
“…Also, they are important information for possible impact prediction with the Earth's magnetosphere, their arrival time as well as their journey in the interplanetary medium (e.g. Möstl & Davies 2013;Möstl et al 2015). The ICME structure also affects the transport of energetic particles in the heliosphere over a large range of energies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…With the triangulation method, it is revealed that fast CMEs impulsively accelerate until even after the X-ray flare maximum, and then rapidly decelerate to a nearly constant speed or gradual deceleration phase (Liu et al 2013), while slow CMEs experience a slow acceleration phase and then travel with a roughly constant speed around the average solar wind level . A CME could also propagate in a non-radial direction (e.g., Wang et al 2004;Gopalswamy et al 2009;Möstl et al 2015;Liewer et al 2015;Wang et al 2015), interact with other CMEs (e.g., Lugaz et al 2009;Gopalswamy et al 2001b;Liu et al 2012Liu et al , 2014 or co-rotating interaction regions (e.g., Reiner et al 1998;Rouillard et al 2010;Liu et al 2016), or rotate in interplanetary space (e.g., Thernisien et al 2006;Liu et al 2010b;Vourlidas et al 2011), which increases difficulty to predict the CME arrival characteristics at the Earth.…”
Section: Introductionmentioning
confidence: 99%